Pengaruh Average Daily Rate dan Nilai Tukar Mata Uang terhadap Revenue Per Available Room di Hotel XYZ - Wayan Suyasa Ariantha; I Gusti Agung Gede Witarsana; Ni Made Suastini (JURNAL BISNIS HOSPITALITI, 2021)
Revenue Per Available Room (RevPAR) at Hotel XYZ has decreased since 2017 to 2019. Hotel XYZ applied Best Average Daily Rate (ADR) to increase the income without reducing the guest satisfaction. This ADR used USD nominal, so the currency exchange rate (dollar to rupiah) will have an effect on RevPAR that should be reported by using rupiah nominal. There was a phenomenon that the increase of ADR and the currency exchange rates were not followed by the increase of RevPAR at Hotel XYZ in 2017 until 2019. The purpose of this research was to analyze the effect of Average Daily Rate (ADR) and the currency exchange rate on Revenue Per Available Room (RevPAR) at Hotel XYZ. This research was a quantitative research and used multiple linier regression analysis techniques, t-test, F test and coefficient of determination test by using SPSS version 23.0 program. In determining the sample of this study, non-probability sampling method was used. The sample used in this study is data from the last 3 years, 2017, 2018, and 2019. The result of the study showed that Average Daily Rate (X1) and the currency exchange rate (X2) had a significant effect on Revenue Per Available Room (Y) at Hotel XYZ, both partially or simultaneously.